Non-pharmacological treatment of depression: a systematic review and evidence map. Issue 6 (11th November 2016) - Farah, Wigdan H; Alsawas, Mouaz; Mainou, Maria; Alahdab, Fares; Farah, Magdoleen H; Ahmed, Ahmed T; Mohamed, Essa A; Almasri, Jehad; Gionfriddo, Michael R; Castaneda-Guarderas, Ana; Mohammed, Khaled; Wang, Zhen; et al.
Abstract : Background: The comparative effectiveness of non-pharmacological treatments of depression remains unclear. Methods: We conducted an overview of systematic reviews to identify randomised controlled trials (RCTs) that compared the efficacy and adverse effects of non-pharmacological treatments of depression. We searched multiple electronic databases through February 2016 without language restrictions. Pairs of reviewers determined eligibility, extracted data and assessed risk of bias. Meta-analyses were conducted when appropriate. Result: We included 367 RCTs enrolling ∼20 000 patients treated with 11 treatments leading to 17 unique head-to-head comparisons. Cognitive behavioural therapy, naturopathic therapy, biological interventions and physical activity interventions reduced depression severity as measured using standardised scales. However, the relative efficacy among these non-pharmacological interventions was lacking. The effect of these interventions on clinical response and remission was unclear. Adverse events were lower than antidepressants. Limitation: The quality of evidence was low to moderate due to inconsistency and unclear or high risk of bias, limiting our confidence in findings. Conclusions: Non-pharmacological therapies of depression reduce depression symptoms and should be considered along with antidepressant therapy for the treatment of mild-to-severe depression. A shared decision-making approach is needed to choose between non-pharmacological therapies based on values, preferences, clinical and social context.